2003
DOI: 10.1016/s0092-8674(03)00688-3
|View full text |Cite
|
Sign up to set email alerts
|

Activated Cdc42 Sequesters c-Cbl and Prevents EGF Receptor Degradation

Abstract: Cdc42 is a Ras-related protein that has been implicated in the control of normal cell growth, and when improperly regulated, in cellular transformation and invasiveness. A variety of extracellular stimuli, including epidermal growth factor (EGF), activate Cdc42. Here, we show that activation of Cdc42 protects the EGF receptor from the negative regulatory activity of the c-Cbl ubiquitin ligase. Activated Cdc42 binds to p85Cool-1 (for cloned-out-of-library)/beta-Pix (for Pak-interactive exchange factor), a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
170
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(178 citation statements)
references
References 33 publications
6
170
0
1
Order By: Relevance
“…However, only when Cdc42 disengages from the ACK2/SH3PX1 complex, presumably because of GTP hydrolysis, would ACK2/SH3PX1 associate with clathrin, which may be necessary to ensure that these sorting participants are properly conveyed to the endosomes. It is interesting that we have also found that Cdc42 regulates the Cbl-catalyzed ubiquitination of EGF receptors (18), which has been shown to be essential for receptor degradation (42,43). Taken together, these results have led us to propose that the EGF-dependent activation of Cdc42 provides a timing mechanism for the sorting and degradation of EGF receptors.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, only when Cdc42 disengages from the ACK2/SH3PX1 complex, presumably because of GTP hydrolysis, would ACK2/SH3PX1 associate with clathrin, which may be necessary to ensure that these sorting participants are properly conveyed to the endosomes. It is interesting that we have also found that Cdc42 regulates the Cbl-catalyzed ubiquitination of EGF receptors (18), which has been shown to be essential for receptor degradation (42,43). Taken together, these results have led us to propose that the EGF-dependent activation of Cdc42 provides a timing mechanism for the sorting and degradation of EGF receptors.…”
Section: Discussionmentioning
confidence: 76%
“…It will be interesting in the future to better understand exactly how Cdc42 activation is maintained for Binding of EGF to the EGF receptor promotes the activation of the Src tyrosine kinase that phosphorylates (P*) and stimulates the GEF activity of Vav2. This in turn leads to the activation of Cdc42, which enables it to engage targets at the plasma membrane like ACK2 and WASP, as well as regulate Cbl through the binding of activated Cdc42 to the Cool-1 (for cloned-out-of-library)/␤-Pix (for PAK-interactive exchange factor) protein (18). The EGF-and Srcdependent phosphorylation of Cdc42 promotes its binding to RhoGDI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar manner, the loss of the direct Cbl TKB-binding site in the CSF-1R (Mancini et al, 2002), as well as the loss of Cbl recruitment to the Kit receptor (Herbst et al, 1995), results in enhanced transforming activity. Multiple additional mechanisms that reduce Cbl-mediated ubiquitination of RTKs, such as enhanced Cbl degradation or sequestration, have been identified (Wong et al, 2002;Bao et al, 2003;Wu et al, 2003;Lee et al, 2004). These observations suggest that loss of a Cbl TKB binding site may be a common mechanism that contributes to full oncogenic activation of RTKs.…”
Section: Loss Of Cbl Ubiquitylation In Oncogenic Rtksmentioning
confidence: 97%
“…New data by Sorkin and coworkers show that EGFR ubiquitination is not required for internalization but plays a role in the targeting of the EGFR to late endosomes and multivesicular bodies for degradation, providing additional mechanistic detail on the role of Cbl in EGFR downregulation (Huang et al, 2007). Interestingly, activated Cdc42 sequesters Cbl away from the EGFR and inhibits its downregulation (Wu et al, 2003). However, there is no evidence linking the effect of activated Cdc42 in EGFR downregulation and signaling in the context of polarized epithelia, and it is not known whether the depolarization of epithelia observed upon expression of activated Cdc42 is related to an increase in EGFR-mediated signaling.…”
Section: How Cancer Hijacks the Epp Machineriesmentioning
confidence: 99%